Small and medium enterprise development for climate adaptation and an inclusive food system in Egypt - Steinhuebel-Rasheed, Linda; Darwish, Maram; Ecker, Olivier (International Food Policy Research Institute, 2025)
Rural households in many low- and middle-income countries remain highly dependent on agriculture and related value chain activities, making them particularly vulnerable to the impacts of climate change. As rising temperatures and increasing climate variability reduce agricultural productivity and income stability, small and medium enterprises (SMEs) are increasingly promoted as a path toward rural development and the transformation of the agrifood systems (AFS). Yet, little is known about whether climate change influences rural households’ decision to start an enterprise to diversify or switch their income sources away from agriculture-related activities in order to adapt to weather risks. We address this research gap by drawing from nationally representative data from the Egypt Labor Market Panel Survey 2023 and estimating a dynamic duration model to explore how heat stress is linked to households’ likelihood to start a (nonfarm) SME. Our findings offer new evidence for climate-responsive rural policy and SME support strategies in vulnerable regions.